Unviability of a special legal regime for the shared custody of children with disabilities in Perú - Camino de Menchaca, María José; Pardo Castro, Mariana; Varsi-Rospigliosi, Enrique (Acta Bioethica, 2023)
In terms of family law, Peruvian legislation contemplates the possibility of shared custody, expressly regulated in the Code of Children and Adolescents, without establishing details on the conditions and forms of application, which is similar in comparative law. Based on bioethical and legal principles, this article analyses the possibility of generating a special regulation for shared custody, focusing on the need to establish special criteria that judges can take into account in specific cases involving children. These criteria should be based on a social model aimed at breaking down the barriers imposed, providing the most appropriate conditions for an integral and full development. In this line of thought, the best interests of the child, the commitment of the parents and the implementation of reasonable accommodations are fundamental.